Law on the analyst’s couch?: the uses of psychoanalytic theory in contemporary U.S. scholarship - Caudill, David S. (Pontificia Universidad Católica del Perú, 2016)
In the U.S. legal context, psychoanalysis is viewed by most scholars (and most judges) as outdated, even unscientific, and there is little room for psychoanalytic expertise in U.S. courts of law. However, there are some scholars who continue to do theoretical work in the conventional Freudian tradition, as well as numerous critical legal theorists who have appropriated the psychoanalytic conceptions of Jacques Lacan in their critiques of the law. This is a brief survey of how these scholars conceive of the law in psychoanalytic terms. Is it the judge being analyzed? Is it the lawyers, or the law students? Is the law itself viewed as subject with an unconscious and with symptoms? Or is it an analysis of legal texts as having an unconscious dimension that is hidden like an ideology? I identify examples of all four frameworks, and conclude that these scholars, notwithstanding their theoretical orientation, have practical goals for law in mind.